Interpretaciâ teksta v funkcionalʹno-stiževom aspekte - Kožina, Margarita N. (Stylistyka, 1992)
Proceeding from the assumption of language as a functioning system and the thesis of the text specificity arising from a number of extra-linguistic features and the imposibility of its exact interpretation based on the purely linguistic ground, the author indicates the necessity of developing a new Jevel of the functional-stylistic analysis of the text. It must te a complex investigation into the stylistic-semantic structure and composition of the text resting upon the data of the adjacent sciences (gnosiology, psychology, logic et al.). There are examples of the scientific text analysis revealing and explaining the style specificity and the systemic nature of speech